Sistem Informasi Geografis untuk Pemetaan Lokasi Rumah Tahfidz Qur’an - Lidya Astuti; Hafid Syafwan; Akmal Nasution (Jurnal Pendidikan Informatika (EDUMATIC), 2022)
Rumah Tahfidz Qur'an is an alternative for people, especially parents who want to educate their children to be able to read the Qur'an. However, the lack of knowledge and community about the location of some third qur'an houses, makes people only include their children in locations throughout the house. This study aims to create a geographic information system to map the location of the Rumah Tahfidz Qur'an, especially in the city of Tanjung Balai. Waterfall is a model used in this study with analysis, design, implementation, and testing, as well as maintenance. The analysis stage was carried out by collecting data on the location of the Rumah Tahfidz Qur'an by observation and interviews. The design used consists of, use case-diagram, class diagram, and flowchart. Testing this system uses black box testing, which aims to see the functionality to the system. Our findings show that there are 41 locations of Rumah Tahfidz Qur'an in the Tanjung Balai city area. The system that we have created has succeeded in providing or mapping the location of the Rumah Tahfidz Qur'an quickly and accurately. In addition, all functional-based on black box testing on this system have been successful and without any errors. This system can be used by society as an information medium in finding the location of the Rumah Tahfidz Qur'an in the Tanjung Balai Kota area.